The doctrine of legitimate expectation in South African labour law - Moila, Phetole Patrick (University of Limpopo (Turfloop Campus), 2010)
The study evaluates the common law position regarding the principle of legitimate expectation at the workplace. Under the common law, the employer had the power to hire and to fire as he or she pleased. The employer could either fire for a good reason or for a bad one or for no reason at all, provided the dismissal was on notice. In other words the employer was not required to show good cause for terminating the contract or to inform them employee of such reasons as they may be or to follow any special procedures before termination. It was not possible for the employee to raise question of legitimate expectation by then. The study exposed the complexity of this principle in our current labour laws. The two schools of thoughts regarding the principle have been analysed herein and a proper recommendation was made.
Thesis (LLM)--University of Limpopo, 2010
Keywords: South African labour law; Dismissal; Labour laws and legislation - South Africa